Concentration of biopetrol synthesized from stearic acid through catalytic cracking using zeolites as catalyst - Nur Aini Liyana, Zakaria (2009)
Biopetrol is an alternative fuel that have same characteristic with the petrol in term of its molecular formula, or to be specifically the octane number of molecules. In this research, the objective is to study the effect of catalyst which is Zeolite to enhance the production of Isooctane from Stearic Acid. The experiment starts with heating the Stearic Acid until it melts at 69.6oC, and then 20 grams of zeolite being added and the heating process proceed until the temperature reached 98oC as the isooctane produce will evaporates. The next experiment is repeated by with different mass of zeolite which is 10 grams, 5 grams and 1 gram. This reaction is called as Catalytic Cracking, where the zeolite will enhance the production of Isooctane. From the result obtained from the Gas Chromatogram result, the percentage of actual concentration of isooctane obtained for 20 g Zeolite is 3.95%, 10g zeolite is 2.769%, 5g zeolite is 3.387% and 1g Zeolite is 2.946%. The highest percentage of Isooctane produced is Stearic Acid distillate with 20g Zeolite, which is 3.95%. This experiment could be more effective by applying dynamic state concept to the process.